Incidence of the financial management in the commercial MiPymes of food products of the city of Machala (Revista revoluciones, 2021)
MiPymes have become one of the largest sources of economic movement in the country, however, their mortality rate is high because they do not last for a long time and do not develop with should be, that is why in the This project intends to carry out an analysis on the impact that a financial department has to promote the development of MiPym in the city of Machala. For this, a quantitative method investigation was carried out, with a descriptive-experimental scope, where a survey was presented aimed at company managers, to confirm their opinion about this influence. With the information it was possible to consider that financial management is necessary to establish decision-making and know its financial status, taking into account a vertical balance analysis that allows it to be compared with the financing of other companies
Keywords: MiPymes; Financial management; financial statement; vertical balance